2022
DOI: 10.1503/cjs.025120
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based differences in letters of recommendation in applications for general surgery residency programs in Canada

Abstract: Background: In Canada, residency programs do not have many objective measures for ranking candidates. Instead, ranking relies on subjective measures such as letters of reference, which can be affected by the genders of the writer and the applicant. Our study assesses letters of recommendation for a general surgery program in Canada to categorize differences in reference letters based on the genders of appli cant and letter writer. Methods:We assessed 215 reference letters from 51 general surgery candidates for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Insufficient same-sex role models or mentors has been cited here as a reason for not pursuing ophthalmology among females who are URM . In general surgery, a study found that female medical students applying to residency had more letters written by female staff, corroborating female sex preferences in mentors . A systematic review in neurosurgery identified that female mentorship was the most cited factor contributing to sex differences in its field .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Insufficient same-sex role models or mentors has been cited here as a reason for not pursuing ophthalmology among females who are URM . In general surgery, a study found that female medical students applying to residency had more letters written by female staff, corroborating female sex preferences in mentors . A systematic review in neurosurgery identified that female mentorship was the most cited factor contributing to sex differences in its field .…”
Section: Discussionmentioning
confidence: 87%
“…11 In general surgery, a study found that female medical students applying to residency had more letters written by female staff, corroborating female sex preferences in mentors. 102 A systematic review in neurosurgery identified that female mentorship was the most cited factor contributing to sex differences in its field. 103 To improve representation, mentorship programs with female and faculty who are URM ought to be developed, recognized, and rewarded in ophthalmology.…”
Section: Discussionmentioning
confidence: 99%
“… 27 In addition to the use of test scores, the use of LORs has been shown to be of high importance in fellowship selection within the field of ophthalmic plastic and reconstructive surgery; however, implicit bias found within LORs can present an additional barrier to applicants not meeting the required threshold. 29 30 31 32 33 Suggestions for addressing this barrier include the use of freely available artificial intelligence tools when writing letters as well as the use of a standard LOR as currently used in the field of emergency medicine, orthopaedic surgery, and otolaryngology. 29 34 The holistic review of an application has been shown to be beneficial to both individuals and programs and the use of a task force can help streamline the process of holistic review for graduate medical education programs.…”
Section: Discussionmentioning
confidence: 99%